PENGARUH GOODWILL, PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Permatasari, Intan; Ratnaningsih, Stephana Dyah Ayu (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study is targeted at analyzing the impact of goodwill, profitability, company size and leverage on company value in mining sector companies verified on the IDX from 2019 - 2023. The sample was taken using a purposive sampling technique, totaling 59. To manage the data using multiple linear regression analysis. from IBM SPSS for this research. The findings of this research indicate that profitability and company size have a significant impact on company value, while leverage and goodwill have no impact on the company value variable..